Organizational commitment, talent management and performance in hospitality industry/ Rajani Kumari Sarangal, Priyanka Sharma and Parikshat Singh Manhas - Sarangal, Rajani Kumari; Sharma, Priyanka; Manhas, Parikshat Singh (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2020)
This paper's primary rationale is to investigate the impact of talent management practices (TMP) on organisational performance (OP) in the hospitality industry. Further, the study also tends to approach the mediating role of organisational commitment (OC) between TMP and OP within the hospitality Industry. The questionnaire method has been administered to gather the data from 440 managers and employees of selected two and three-star hotels. Statistical tools, i.e. EFA, CFA and SEM, were utilised to analyse the data. The study finds that TMP significantly and positively influences OP. Further, the study also verified that OC acts as a mediator between TMP and OC. The study has been restricted to North India, which includes two and three stars properties only; it should be extended in other sectors in the future. This study has significant value because it identifies that good exercise of TMP in hotels will lead to high performance. The present research indicates the practice for a more thorough TMP as it creates more committed employees, which enhances their performance by escalating their skills, capabilities, and knowledge and builds up self-confidence among them, which is an advantage today's competitive market.